The LEGO story : how a little toy sparked the world's imagination - Andersen, Jens, 1955- (Mariner Books, 2022)
"The extraordinary inside story of the LEGO company--producer of the most beloved and popular toy on the planet--based on unprecedented access to the founding family that still owns the company, chronicling the brand's improbable journey to become the empire that it is today"--